Uncertainty Tolerance in Physiotherapists - Aday Infante Guedes; María del Pilar Etopa Bitata; María del Pino Quintana Montesdeoca (Universidad de Murcia, 2024)
Although uncertainty is common in the field of physiotherapy, little research has been conducted on the topic of uncertainty tolerance (UT). This study builds on previous research that explored UT in novice physiotherapists and identified their educational needs in relation to UT using the self-developed "Tolerance to Uncertainty in Physiotherapy" (TUP) questionnaire. The present work aims to explore UT in experienced physiotherapists, identify their educational needs regarding uncertainty management, and compare them with novice physiotherapists. A cross-sectional quantitative observational study was conducted involving 40 physiotherapists with an average work experience of 11.9 (7.52) years participated. The results show that the evaluated physiotherapists had a medium-high UT with 51 points (5.99) on the TUP scale. Years of experience could not be confirmed as a good predictor of UT, although a trend towards improved UT was observed (r= -0.075, p-value = 0.645). Experienced physiotherapists were less nervous or anxious about unknown diagnoses and had less difficulty switching off mentally. However, they were in agreement with novice physiotherapists in terms of requesting more diagnostic tests or more frequent appointments. Implementing educational programmes to improve UT during the training period and in experienced professionals is essential.